Pengaruh kualitas website dan kepercayaan terhadap kepuasan pelanggan bukalapak di Surabaya - Aufar, Muhammad Zharfandi; Soebiantoro, Ugy (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The rapid development of technology today makes the internet an important role in doing various things. Internet and technology have provided a change in the activities of its users to be more effective and efficient. With the internet, users can carry out activities wherever and whenever they want, regardless of time and place. The internet provides convenience in the aspects of trading and digital purchases that are supported by e-commerce in Indonesia. The large level of digital buying in Indonesia has made changes in buying behavior now and in the past. This study aims to analyze the quality of the website and trust in Bukalapak's customer satisfaction. The sample used in this research is Bukalapak customers in Surabaya who have transacted with 80 respondents. The sampling technique used is non- probability sampling. The analytical technique used is Partial Least Square (PLS). Test the validity and reliability of the data using data collected from the results of the questionnaire using the Likert technique.Based on the research that has been done, it shows that Website Quality has a positive influence on Customer Satisfaction and Trust has a positive influence on Bukalapak Customer Satisfaction in Surabaya.